1987
DOI: 10.1073/pnas.84.24.9257
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the chromosome translocation breakpoint junction of the t(14;19) in chronic lymphocytic leukemia.

Abstract: Our laboratory has reported that t(14;19)(q32; q13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 21 publications
2
54
0
Order By: Relevance
“…The constitutive NF-kB activity seen in most haematological disorders occurs through several mechanisms, including the chromosomal translocation and subsequent overexpression of BCL-3 in a subset of human B-cell chronic lymphotic leukaemias (McKeithan et al, 1987) and mutations of the IkBa gene that impair its inhibitory function in some cases of Hodgkin's lymphomas (Cabannes et al, 1999;Emmerich et al, 1999;Jungnickel et al, 2000). Gene amplification of NIK or loss of function mutations for inhibitory signalling molecules such as TRAF3 and CYLD have been reported in multiple myelomas (Annunziata et al, 2007;Keats et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive NF-kB activity seen in most haematological disorders occurs through several mechanisms, including the chromosomal translocation and subsequent overexpression of BCL-3 in a subset of human B-cell chronic lymphotic leukaemias (McKeithan et al, 1987) and mutations of the IkBa gene that impair its inhibitory function in some cases of Hodgkin's lymphomas (Cabannes et al, 1999;Emmerich et al, 1999;Jungnickel et al, 2000). Gene amplification of NIK or loss of function mutations for inhibitory signalling molecules such as TRAF3 and CYLD have been reported in multiple myelomas (Annunziata et al, 2007;Keats et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Four months after starting treatment with dasatinib, the patient was also evaluated for CML: bone marrow analysis showed complete cytogenetic response and undetectable bcr-abl transcript by real-time PCR. 1 This case report leaves us with some open questions: firstly, what mechanisms of dasatinib are involved in gynecomastia? Secondly, why did our patient develop gynecomastia during dasatinib treatment and not when taking imatinib?…”
mentioning
confidence: 99%
“…The chromosomal rearrangement of the immunoglobulin heavy chain (IGH) gene locus resulted in upregulated expression of a new gene, named BCL3, encoding a protein member of the IkB family. 1 It was then reported that t(14;19) was not entirely specific to CLL, because it was also found in other types of chronic B-cell malignancies (for review, see Soma et al 2 ). The Groupe Francophone de Cytogénétique Hématologique (GFCH) collected 43 chronic lymphoproliferative disorders with t(14; 19) or variant BCL3-translocations between 1988 and 2007, to analyze to what extent this uncommon abnormality could define a subgroup among B-cell malignancies, and to document the consequences of the rearrangement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B-cell leukemia/lymphoma 3 (Bcl-3) is a protooncogene and was initially identified from the patients with chronic lymphocytic leukemia (B-CLL) (McKeithan et al, 1987;Ohno et al, 1990). Elevated Bcl-3 was found in a number of solid tumors, as well as in leukemia and lymphoma.…”
Section: Introductionmentioning
confidence: 99%